2005
DOI: 10.14411/eje.2005.052
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild predation among aphidophagous predators

Abstract: Abstract. Since the publication of papers by Polis et al. (1989Polis et al. ( , 1992, intraguild predation (IGP) has been considered in numerous systems and a growing number of papers have been published, demonstrating the ubiquity and the importance of this interaction. It appears that aphidophagous guilds constitute especially favourable systems for IGP. Temporal and spatial distributions of aphids promote interactions, such as IGP, among natural enemies. However, despite extensive laboratory and field studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
149
0
13

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 150 publications
(163 citation statements)
references
References 105 publications
1
149
0
13
Order By: Relevance
“…Other studies also reported that additive models for combined predator effects cannot account for non-linearity in combined functional response introduced by behavioral interactions between predators and prey (Soluk 1993; see also Colton 1987 for similar conclusions when one predator interacts with two prey species). However, (1) we estimated behavioral parameters and tested model predictions under similar experimental conditions (e.g., growth chamber, temperature, prey size and age), (2) switching generally occurs when eating the IG prey is risky for the IG predator (Lucas 2005); this is not the case for C. maculata preying on A. aphidimyza larva (Lucas et al 1998), and (3), in another study (A. Sentis, J. L. Hemptinne and J. Brodeur, unpublished manu- v www.esajournals.org script), we investigated the effect of M. persicae density on A. aphidimyza intraguild predation along a temperature gradient and concluded that model predictions were well supported by empirical results. Altogether, this suggests that an insufficient sampling effort probably explains the divergence between model predictions and empirical results at the highest EG prey density.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies also reported that additive models for combined predator effects cannot account for non-linearity in combined functional response introduced by behavioral interactions between predators and prey (Soluk 1993; see also Colton 1987 for similar conclusions when one predator interacts with two prey species). However, (1) we estimated behavioral parameters and tested model predictions under similar experimental conditions (e.g., growth chamber, temperature, prey size and age), (2) switching generally occurs when eating the IG prey is risky for the IG predator (Lucas 2005); this is not the case for C. maculata preying on A. aphidimyza larva (Lucas et al 1998), and (3), in another study (A. Sentis, J. L. Hemptinne and J. Brodeur, unpublished manu- v www.esajournals.org script), we investigated the effect of M. persicae density on A. aphidimyza intraguild predation along a temperature gradient and concluded that model predictions were well supported by empirical results. Altogether, this suggests that an insufficient sampling effort probably explains the divergence between model predictions and empirical results at the highest EG prey density.…”
Section: Discussionmentioning
confidence: 99%
“…However, this might not be the case in other systems where the benefit/cost ratio of eating the IG prey varies. Lucas (2005) proposed four types of IGP: (1) opportunistic, when IGP is a fortuitous event, (2) nutritional, when nutritional benefits are associated with the eating of an IG prey, (3) competitive, when eating the IG prey eliminates an important competitor, and (4) protective, when eating the IG prey eliminates a potential predator under conditions of symmetrical IGP. In the first type, the IG predator does not explicitly search for IG prey, whereas in the three others it actively hunts IG prey because of the benefits of killing or eating them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations